Crohn's Disease Accompanied with Small Intestinal Extramedullary Plasmacytoma - Hanawa, Yoshinori (Intern Med, 2019)
We herein present the case of an immunocompetent 63-year-old man who had previously undergone resection of Crohn's disease (CD)-related small intestinal obstruction more than 30 years ago. He had not been receiving any medication for many years, but had recently started to suffer from ileus. A stenosed site of ileo-cecal anastomosis was identified and therefore was surgically resected, which was diagnosed as CD with small intestinal extramedullary plasmacytoma (EMP). The subsequent progression of CD was successfully controlled by anti-TNFα agents without any recurrence of EMP for over 3 years, implying the clinical benefit and safety of the biological therapy. This was the first known case of a patient who received anti-TNFα agents after a resection of small intestinal EMP accompanied with CD.